Higher education in private universities of Bangladesh: A study on female students' enrollment behavior - Khan, Rezwanul Huque; Mridha, Ali Haider Al Mamun; Barua, Suborna (BRAC University, 2011)
This paper investigates the enrollment behavior of the female students of private universities in Bangladesh. By collecting data from a sample of 900 female students of twelve private universities classified into two strata, researchers conducted reliability test, descriptive analysis, chi-square and ANOVA tests and identified a number of key findings as to the enrollment behavior of female students. The research shows that the female students mostly prefer BBA program followed by BA in English. In the faculty of Science and Engineering, BS in Pharmacy gets the highest preference. In Post Graduate level MBA and M.A in English are the preferred subjects. The most important factor for the female students of one strata (top ranked private universities) during admission is the quality of teaching of the university, followed by the image of that university. On the contrary, the female students of other private universities look for lower tuition fees of their preferred program. For the both strata parents' decision has a significant influence. Finally, the female students of top ranked universities are highly satisfied with the image of their universities while the female students of other universities are dissatisfied with the overall performance of their universities.